The Archival Documents on the Activities of the Buryat-Mongolian State Institute of Culture in the 1930s - Ts. P. Vanchikova; M. V. Ayusheeva (Библиосфера, 2023)
The purpose of the article is to study the written sources appeared as a result of activities of the Buryat-Mongolian State Institute of Culture - the successor of the Buryat-Mongolian scientific committee and kept now in the Centre of Oriental manuscripts and xylographs of the Institute for Mongolian, Buddhist and Tibetan Studies of the Siberian Branch of the Russian Academy of Sciences. The article highlights the history of the Institute of Culture as the main research center for the study of the Buryat-Mongolian Autonomous Socialist Soviet Republic in the 1930s, archival documents characterizing the history of the creation of the library and library collections, publishing activities and information about unpublished works, for example about the manuscript version of the bibliography, including 602 entries. Through the integrated use of content analysis methods for text arrays in archival sources and the reconstruction of separate events in chronological order, the main directions of the Institute’s activities have been determined. In spite of the complicated period in the history of the country the process of collecting books in Tibetan, Mongolian and in Old Slavonic was not stopped. During 7 years of functioning, the Institute was able to develop its scientific potential, form an extensive source base on the history, folklore and ethnography of the Buryat people, and successfully solve the issues of language construction. Archival materials presented by various documents: articles, monographs, drafts, field materials, both published and unpublished, are of great scientific importance and are of interest to historians of science, folklorists, and ethnologists.